Population panmixia and demographic expansion of a highly piscivorous marine fish Scomberomorus niphonius - S. Kitada; K. Nakajima; K. Hamasaki (Journal of Fish Biology, 2017)
Population structure and demographic history of the Japanese Spanish mackerel Scomberomorus niphonius a highly piscivorous and migratory marine fish, were assessed using mitochondrial DNA control region sequences ( n = 720) and microsatellite genotypes at five loci ( n = 1331) for samples collected on Japanese coasts from 2001 to 2010. The population structure was panmictic and the haplotype and allele frequencies were temporally stable even during the recent recovery process. Demographic expansion was strongly supported throughout the Pleistocene, suggesting that the oscillating glacial and interglacial climate conditions in the Pleistocene had no substantial impact on the demographic history of S. niphonius .

Genetic effects of hatchery fish on wild populations in red sea bream Pagrus major (Perciformes, Sparidae) inferred from a partial sequence of mitochondrial DNA - K. Hamasaki; S. Toriya; H. Shishidou; T. Sugaya; S. Kitada (Journal of Fish Biology, 2010)
Variation in the mitochondrial DNA transcriptional control region sequence was investigated in wild and hatchery‐released red sea bream Pagrus major from Kagoshima Bay, where an extensive hatchery‐release programme has been conducted for >30 years. The programme has successfully augmented commercial catches in the bay (released juveniles have been produced from the captive broodstock, repeatedly used over multiple generations). Samples were also obtained from outside the bay, where limited stocking has occurred. Genetic diversity indices measured as number of haplotypes, haplotype richness, haplotype diversity and nucleotide diversity were lower in hatchery‐released fish than in wild fish. Genetic differences in wild fish from the bay, especially in the inner bay, compared with fish from outside the bay were detected in terms of decreased genetic diversity indices and changed haplotype frequencies. Unbiased population pair‐wise F ST estimates based on an empirical Bayesian method, however, revealed low genetic differentiation between samples from the bay and its vicinity. Mixed stock identification analyses estimated the proportion of hatchery‐released fish in wild populations in the inner and central bays at 39·0 and 8·7%, respectively, although the precision of the estimates was very low because of the small genetic differentiation between populations and relatively small sample sizes. Hence, the long‐term extensive hatchery release programme has affected the genetic diversity of wild populations in the bay; however, the genetic effects were low and appeared to remain within the bay.

Lafutidine can improve the quality of gastric ulcer healing in humans: a randomized, controlled, multicenter trial - K. Higuchi; T. Watanabe; K. Tominaga; M. Shiba; K. Nakagawa; H. Uno; K. Kitada; H. Satoh; S. Chono; N. Oshitani; Y. Fujiwara; T. Arakawa (Inflammopharmacology, 2006)

Response to ADP-Ribose by Activation of TRPM2 in the CRI-G1 Insulinoma Cell Line - K. Inamura; Y. Sano; S. Mochizuki; H. Yokoi; A. Miyake; K. Nozawa; C. Kitada; H. Matsushime; K. Furuichi (The Journal of Membrane Biology, 2003)

Peripheral nerve regeneration through alginate gel: analysis of early outgrowth and late increase in diameter of regenerating axons - T. Hashimoto; Y. Suzuki; M. Kitada; K. Kataoka; S. Wu; K. Suzuki; K. Endo; Y. Nishimura; C. Ide (Experimental Brain Research, 2002)

Changes in urinary 6β-hydroxycortisol/cortisol ratio after birth in human neonates - H. Nakamura; M. Hirai; S. Ohmori; Y. Ohsone; T. Obonai; K. Sugita; H. Niimi; M. Kitada (European Journal of Clinical Pharmacology, 1998)

Molecular evolution of human paramyxoviruses - K. Miyahara; S. Kitada; M. Yoshimoto; H. Matsumura; M. Kawano; H. Komada; M. Tsurudome; S. Kusagawa; M. Nishio; Y. Ito (Archives of Virology, 1992)